The Effect of Dividend Policy Measurement on Stock Price Volatility in the Manufacturing Sector in Indonesia - Meriem Della Sadrina; Henny Setyo Lestari (Peneliti.net, 2022)
The problem of this research was dividend policy had important role to stock price volatility and there was factors that important as a measurement to made a financial planning decision. The objectives of this research was to analyze the effect of stock price volatility in 33 Manufacturing Companies Listed on the Indonesia Stock Exchange for the Period of 2016 – 2020 The methodology of this research was panel data regression analysis resulting Random Effect Model that used the type of time series data and cross section through the data processing program used EViews 9, with total of 33 Manufacturing CompaniesFinding and contribution of this research were div, dividend payout ratio, dividend yield, firm size, leverage, earnings per share variables simultaneously had a significant effect on the variable stock price volatility. ividend payout ratio, dividend yield, firm size and leverage variable did not have a significant effect, while the earnings per share variable had negatively significant influence to the stock price volatility. Research implication in this research was can be reference for company management in order to increase stock price volatility by adding more concern to a variabel earning per share that had significant impact to stock price volatility and also for Investor as a consideration on investment determination to predict companies that can give a maximum yield of profit.